Large vs. Small NHC Ligands in Nickel(0) Complexes: The Coordination of Olefins, Ketones and Aldehydes at [Ni(NHC)2]. Issue 33 (14th July 2020) - Tendera, Lukas; Schaub, Thomas; Krahfuss, Mirjam J.; Kuntze‐Fechner, Maximilian W.; Radius, Udo
Abstract : Investigations concerning the reactivity of Ni(0) complexes [Ni(NHC)2 ] of NHCs ( N ‐heterocyclic carbene) of different steric demand, Mes2 Im (= 1, 3‐dimesitylimidazoline‐2‐ylidene) and i Pr2 Im (= 1, 3‐di iso propyl‐imidazoline‐2‐ylidene), with olefins, ketones and aldehydes are reported. The reaction of [Ni(Mes2 Im)2 ] 1 with ethylene or methyl acrylate afforded the complexes [Ni(Mes2 Im)2 (η 2 ‐C2 H4 )] 3 and [Ni(Mes2 Im)2 (η 2 ‐( C, C )‐H2 C=CHCOOMe)] 4, as it was previously reported for [Ni2 ( i Pr2 Im)4 ( µ‐( η 2 :η 2 ) ‐COD)] 2 as a source for [Ni( i Pr2 Im)2 ]. In contrast to 2, complex 1 does not react with sterically more demanding olefins such as tetramethylethylene, 1, 1‐diphenylethylene and cyclohexene. The reaction of [Ni(NHC)2 ] with more π ‐acidic ketones or aldehydes led to formation of complexes with side‐on η 2 ‐( C, O )‐coordinating ligands: [Ni( i Pr2 Im)2 (η 2 ‐O=CH t Bu)] 5, [Ni( i Pr2 Im)2 (η 2 ‐O=CHPh)] 6, [Ni( i Pr2 Im)2 (η 2 ‐O=CMePh)] 7, [Ni( i Pr2 Im)2 (η 2 ‐O=CPh2 )] 8, [Ni( i Pr2 Im)2 (η 2 ‐O=C(4‐F‐C6 H4 )2 )] 9, [Ni( i Pr2 Im)2 (η 2 ‐O=C(OMe)(CF3 ))] 10 and [Ni(Mes2 Im)2 (η 2 ‐O=CHPh)] 11, [Ni(Mes2 Im)2 (η 2 ‐O=CH(CH(CH3 )2 ))] 12, [Ni(Mes2 Im)2 (η 2 ‐O=CH(4‐NMe2 ‐C6 H4 ))] 13, [Ni(Mes2 Im)2 (η 2 ‐O=CH(4‐OMe‐C6 H4 ))] 14, [Ni(Mes2 Im)2 (η 2 ‐O=CPh2 )] 15 and [Ni(Mes2 Im)2 (η 2 ‐O=C(4‐F‐C6 H4 )2 )] 16 . The reaction of 1 and 2 with these simple aldehydes and ketones does not lead to a significantly different outcome, but NHC ligand rotation is hindered for the Mes2 Im complexes 3, 4 and 11–16 according to NMR spectroscopy. The solid‐state structures of 3, 4, 11 and 12 reveal significantly larger CNHC ‐Ni‐CNHC angles in the Mes2 Im complexes compared to the i Pr2 Im complexes. As electron transfer in d 8 ‐ (or d 10 ‐) ML2 complexes to π ‐acidic ligands depends on the L–M–L bite angle, the different NHCs lead thus to a different degree of electron transfer and activation of the olefin, aldehyde or ketone ligand, i.e., [Ni( i Pr2 Im)2 ] is the better donor to these π ‐acidic ligands. Furthermore, we identified two different side products from the reaction of 1 with benzaldehyde, trans ‐[Ni(Mes2 Im)2 H(OOCPh)] 17 and [Ni2 (Mes2 Im)2 (µ2 ‐CO)(µ2 ‐η 2 ‐ C, O ‐PhCOCOPh)] 18, which indicate that radical intermediates and electron transfer processes might be of importance in the reaction of 1 with aldehydes and ketones. Abstract : The reactivity of [Ni(Mes2 Im)2 ] 1 and [Ni( i Pr2 Im)2 ] (as provided by [Ni2 ( i Pr2 Im)4 ( µ‐( η 2 :η 2 ) ‐COD)] 2 ) towards simple olefins, ketones, and aldehydes is reported. This study demonstrates how substrate binding to bis‐NHC nickel complexes can be fine‐tuned upon a change of the sterics of the NHC ligand.